2019
DOI: 10.1590/1981-6723.04418
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and antibacterial activity and preliminary toxicity analysis of four varieties of avocado (Persea americana Mill.)

Abstract: The antioxidant and antibacterial activity and toxicity of natural products can change according to plant variety, as well as the part of the plant which is analyzed. In this study, peel, pulp and seed of four avocado varieties (Quintal, Fortuna, Margarida, and Hass) were analyzed for antioxidant and antibacterial properties and toxicity. There are few studies in the literature comparing these three first varieties. Antioxidant capacity was measured using the DPPH (2,2-diphenyl-1-picrylhydrazil), ABTS [2,2'-az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 21 publications
(30 reference statements)
3
12
0
1
Order By: Relevance
“…The results determined that the peel showed a better bactericidal and bacteriostatic effect over the Gram-positive. However, the different ethanolic extracts also demonstrated activity against Gram-negative bacteria [109].…”
Section: Drugs and Bioactive Compoundsmentioning
confidence: 98%
“…The results determined that the peel showed a better bactericidal and bacteriostatic effect over the Gram-positive. However, the different ethanolic extracts also demonstrated activity against Gram-negative bacteria [109].…”
Section: Drugs and Bioactive Compoundsmentioning
confidence: 98%
“… 13 Besides, they are an important source of bioactive compounds with high antioxidant activity, which makes them highly attractive for the production of active food packaging. 15 Other uses reported in the literature include the use of ASs to produce biodiesel 16 , 17 or for the production of carbonized materials used as absorbents. 18 However, there is no information in the literature on the application of avocado byproducts in the packaging field.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that different parts of the avocado plants contain potent phenolic antioxidants such as chlorogenic-, quinic-, succinic-, pantothenic-, abscisic-, ferulic-, gallic-, sinapinic-, p -coumaric-, gentisic-, protocatechuic-, 4-hydroxybenzoic-, and benzoic- acids, quercetin, quercetin-3-glucoside, quercetin-3-rhamnoside, vanillin, p -coumaroyl-D-glucose, catechins, (−)-epicatechin, and procyanidins (Table 3) [2,28,84,89,90,91,92,93,94,95,96,97]. Among the different parts of avocado investigated in several studies, leaf, peel, and seed extracts have shown consistently greater antioxidant capacity compared to that of the pulp [84,91,94,96,97,98,99,100,101,102,103,104,105,106]. Due to the presence of higher catechin, epicatechin, leucoanthocyanidin, triterpenes, furoic acid, and proanthocyanidin contents, avocado seed extracts have been reported to display greater antioxidant capacity [62,74].…”
Section: Introductionmentioning
confidence: 99%